Nietzsche: Thus Spoke Zarathustra - Pippin, Robert (Cambridge University, 2013)
Nietzsche regarded 'Thus Spoke Zarathustra' as his most important work, and it has had an enormous influence on subsequent culture. This edition offers a new translation, which captures the text's poetic brilliance, together with an introduction which discusses many of the most important interpretative issues raised by the work.